(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
The purpose of this study was to determine the results of the evaluation of the South Minahasa District Office of Transportation Staff after participating in an education and technical training program. There are still many obstacles that do not match the results of the evaluation. Utilization of facilities at the time of the implementation of the education and training program both from participants, namely the employees of the Transportation Department of South Minahasa Regency and from the organizers themselves have not been maximized. In this study, the authors used a qualitative approach with the type of descriptive research. In this study primary data were obtained by interview and observation methods while secondary data using literature and documentation research methods. The results of this study indicate that the education and training program has not fully met the target in presenting good changes in employees for the progress of the South Minahasa District Transportation Office. This can be seen based on the results of the evaluation after following the education and training program based on the focus of education research and training regarding the four evaluation indicators as stated by Daniel Stufflebeam. Researchers provide advice on this research that is paying more attention to each employee placement along with the type of education and training programs participated by each employee in order to create professional and good performance in accordance with the demands of each field of staff of the South Minahasa District Transportation Department. Keywords: Evaluation, Education, Training Programs.